Generation of surface oscillations of semiconductor structures by charged particle flows - Serkov, A. A.; Breslavets, V. S.; Breslavets, J. V.; Yakovenko, I. V. (Національний університет "Полтавська політехніка імені Юрія Кондратюка", 2025)
The results of the work determine the degree of influence of flows of charged particles induced by external electromagnetic radiation on the performance of communication equipment. The aim is to determine the conditions for the development of hydrodynamic instabilities of electrostatic oscillations in communication system devices containing semiconductor layers surrounded by media with different electromagnetic properties. The following results are obtained: A mechanism for the occurrence and development of surface electrostatic oscillation (plasmon) instabilities is proposed under conditions where the interaction of electromagnetic oscillations and a flow of charged particles generated by external electromagnetic radiation is ensured by the presence of a boundary. Specific features of the transformation of the spectral kharacteristics of the energy of transition radiation associated with the presence of an interface between media with different electromagnetic properties in open-type radiophysical systems are determined. A new physical mechanism for the generation and amplification of surface electromagnetic oscillations by flows of charged particles, the characteristics of which are determined by the properties of the interface between conductive solids, is developed. Conclusion. The criteria for the occurrence and development of surface plasmon instabilities associated with the nonequilibrium of electronic systems obtained in the work are realized in conductive solids. Therefore, they can be used in the development of active devices of semiconductor electronics designed to amplify, generate and convert electromagnetic oscillations in the millimeter and submillimeter ranges. The comparative analysis of the increments of beam-plasma instabilities of various branches of electrostatic oscillations during the motion of a particle flow along the normal or along the interface of media, carried out in the work, allows us to solve the problems of optimizing existing mechanisms for amplifying oscillations in structures used in modern radiophysics (MDS, MOS, various types of p-n junctions).

Результати роботи визначають рівень впливу потоків заряджених частинок, наведених зовнішнім електромагнітним випромінюванням, на робочі характеристики засобів зв'язку. Мета статті – визначення умов розвитку гідродинамічних нестійкостей електростатичних коливань у пристроях систем зв'язку, що містять напівпровідникові шари, оточені середовищами з різними електромагнітними властивостями. The following results are obtained: Запропоновано механізм виникнення та розвитку нестійкостей поверхневих електростатичних коливань (плазмонів), в умовах, коли взаємодія електромагнітних коливань та потоку заряджених частинок, створюваних зовнішнім електромагнітним випромінюванням, забезпечується наявністю кордону. Визначено специфічні особливості трансформації спектральних характеристик енергії перехідного випромінювання, пов'язані з наявністю межі поділу середовищ з різними електромагнітними властивостями у радіофізичних системах відкритого типу. Розроблено новий фізичний механізм генерації та посилення поверхневих електромагнітних коливань потоками заряджених частинок, характеристики яких визначаються властивостями межі розділу твердих тіл, що проводять. Conclusion. Отримані в роботі критерії виникнення та розвитку нестійкостей поверхневих плазмонів, пов'язані з нерівноважністю електронних систем, реалізуються у твердих тілах, що проводять. Тому вони можуть бути використані при розробці активних пристроїв напівпровідникової електроніки, призначених для посилення, генерування та перетворення електромагнітних коливань міліметрового та субміліметрового діапазонів. Проведений у роботі порівняльний аналіз інкрементів пучково-плазмових нестійкостей різних гілок електростатичних коливань при русі потоку частинок за нормаллю або вздовж межі розділу середовищ, дозволяє вирішувати завдання оптимізації існуючих механізмів посилення коливань у структурах, що використовуються в сучасній радіофізиці (МДП, МОП, різних p-n переходів).
Генерація поверхнівних коливань напівпровідникових структур потоками заряжених часток
Keywords: beam instability of electrostatic oscillations; semiconductor components; induced current; electromagnetic radiation; surface oscillations; пучкова нестійкість електростатичних коливань; напівпровідникові комплектуючі; наведений струм; електромагнітне випромінювання; поверхневі коливання